2013
DOI: 10.4025/actasciagron.v35i1.15622
|View full text |Cite
|
Sign up to set email alerts
|

Association between glucosinolate concentration and injuries caused by cabbage stink bugs Eurydema spp. (Heteroptera: Pentatomidae) on different Brassicas

Abstract: In 2010, we were determining the contents of glucosinolates in different Brassicas in order to study their influence on feeding of cabbage stink bugs (Eurydema spp.) and the consequent extent of damage. We confirmed that glucosinolates content depends on plant species, plant organs and the time of sampling. In the samples aliphatic glucosinolates (glucoiberin, progoitrin, epiprogoitrin, epiprogoitrin, sinigrin, gluconapin, glucoraphenin, sinalbin) prevailed. Glucobrassicin, an important indolic glucosinolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Additionally, despite a few previous reports of contrasting roles of two classes of glucosinolates namely, aliphatics and indolics in conferring resistance or susceptibility against insect herbivory ( De Vos et al, 2008 ; Gols et al, 2008 ; Newton et al, 2009 ; Kos et al, 2011 ; Bohinc et al, 2013 ), our PCA-based approach didn’t recognize any definitive patterns in the contents of either of these two classes of glucosinolates and feeding preference of DBM larvae. This observation suggested that DBM’s feeding preference is not restricted to any particular classes of glucosinolates in our study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, despite a few previous reports of contrasting roles of two classes of glucosinolates namely, aliphatics and indolics in conferring resistance or susceptibility against insect herbivory ( De Vos et al, 2008 ; Gols et al, 2008 ; Newton et al, 2009 ; Kos et al, 2011 ; Bohinc et al, 2013 ), our PCA-based approach didn’t recognize any definitive patterns in the contents of either of these two classes of glucosinolates and feeding preference of DBM larvae. This observation suggested that DBM’s feeding preference is not restricted to any particular classes of glucosinolates in our study.…”
Section: Discussionmentioning
confidence: 64%
“…This observation suggested that DBM’s feeding preference is not restricted to any particular classes of glucosinolates in our study. Together, all these results of laboratory and field experiments indicated that the insect–herbivore interaction is dynamically dependent on the genotype specific glucosinolate profiles as evident by its differential influence on the feeding behavior and damage levels of various generalist and specialist insects ( Mauricio, 1998 ; Li et al, 2000 ; Barth and Jander, 2006 ; Bohinc et al, 2013 ).…”
Section: Discussionmentioning
confidence: 90%
“…The role of sinigrin as an oviposition stimulant for the E. ornatum female has never been reported in the past. A previous study on the responses of this hemipteran to the glucosinolate pattern of different Brassica crops did, however, highlight the importance of having a high content of aliphatic compounds, such as progoitrin, epiprogoitrin, gluconapin and glucoraphanin, and of the indole glucobrassicin in order to reduce the extent of damage, although the effects also depended on plant age (Bohinc et al 2013).…”
Section: Herbivore Responses To Glucosinolate Patternsmentioning
confidence: 83%
“…As our research shows, the method is more efficient in systems of production where mid-late genotypes of cabbage are grown. As we found out, due to the spectrum of different factors (among others also glucosinolate content [45,46]), susceptibility of plants to damage by harmful organisms during the growth period varies. By using mixed crops as a means to reduce damage on the main crops, the said method could be used in different regions of Slovenia and thus override the influence of environmental factors on trap crops as well as the bionomy of the said harmful species itself [47].…”
Section: Discussionmentioning
confidence: 99%